Validating a mobile application for anemia prevention: Insights from expert feedback on AneMia_Prev® - Rahayu, Sri; Said, Mohamed Saifulaman Mohamed; Sansuwito, Tukimin Bin; Mulyono, Sigit (Jurnal Keperawatan Padjadjaran, 2025)
Background: Anemia remains a critical public health issue among adolescents, particularly in developing countries such as Indonesia. Poor nutritional knowledge and limited awareness of anemia-related symptoms, etiology, and prevention exacerbate this condition. Mobile health (mHealth) technologies have the potential to address these gaps through accessible, engaging, and scalable education tools. This study aimed to validate the content of AneMia_Prev®, a mobile application designed as an educational tool to enhance adolescent knowledge on the prevention of anemia. Methods: A Delphi technique was employed involving two rounds of expert panel review. Twelve experts with clinical and academic backgrounds in nursing and public health evaluated the content of AneMia_Prev® based on relevance, clarity, layout, illustrations, language, and motivational features. The Content Validity Index (CVI) and modified kappa statistics were used to assess inter-rater agreement and content adequacy. Data were collected through an online survey using a 17-item validated questionnaire. Results: In the first round, all 17 items achieved excellent content validity with I-CVI values ranging from 0.87 to 1.00 and kappa values above 0.87. Following minor expert recommendations, a revised version of the application was re-evaluated, resulting in unanimous ratings of excellence (I-CVI = 1.00; kappa > 0.92 for all items). Experts emphasized the application’s innovation, relevance, and potential to promote anemia awareness among adolescents. Conclusion: AneMia_Prev® demonstrated excellent content validity and is considered suitable for educational interventions targeting anemia prevention among adolescents. Future research is recommended to assess semantic validation, cognitive impact, and learning outcomes among adolescent users to further refine the tool and evaluate its effectiveness in real-world settings.